LOCAL METHODS OF TREATING ANEMIA IN WOMEN - Inomov Kodirxon Saidmamatovich (Web of Journals Publishing, 2025)
This article explores local and traditional approaches to treating anemia in women, especially in resource-limited and rural settings. By analyzing both cultural practices and scientific evaluations of natural remedies, the article aims to assess their effectiveness, benefits, and limitations. The article also integrates recent data and field studies to discuss how these methods may complement modern medical treatments.
Keywords: Anemia in women, traditional remedies, iron deficiency, herbal medicine, nutrition, local health practices, reproductive health, rural healthcare, dietary interventions, women’s health.